2018
DOI: 10.3390/foods7100172
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Food Hydrolyzed Proteins and Peptides to Chelate Iron or Calcium and Enhance their Absorption

Abstract: Iron and calcium are two essential micronutrients that have strong effects on nutrition and human health because of their involvement in several biological and redox processes. Iron is responsible for electron and oxygen transport, cell respiration, and gene expression, whereas calcium is responsible for intracellular metabolism, muscle contraction, cardiac function, and cell proliferation. The bioavailability of these nutrients in the body is dependent on enhancers and inhibitors, some of which are found in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(79 citation statements)
references
References 117 publications
(135 reference statements)
2
72
0
2
Order By: Relevance
“…Lactic acid bacteria have also been employed in different food sources as seeds to produce angiotensin converting enzyme inhibitor (ACEI) peptides. These peptides are the result of different conditions, such as proteases or strain used, duration of fermentation, pH, and others [ 38 , 39 ]. TSMDF showed almost ten-fold higher ACEI capacity than TSMD.…”
Section: Discussionmentioning
confidence: 99%
“…Lactic acid bacteria have also been employed in different food sources as seeds to produce angiotensin converting enzyme inhibitor (ACEI) peptides. These peptides are the result of different conditions, such as proteases or strain used, duration of fermentation, pH, and others [ 38 , 39 ]. TSMDF showed almost ten-fold higher ACEI capacity than TSMD.…”
Section: Discussionmentioning
confidence: 99%
“…secondary metabolites) such as carotenoids and polyphenols have antioxidant properties, meanwhile, they also possess pro-oxidant function due to the formation of peroxides [12, 19]. Phenoxyl radicals, often quinones and semiquinones, are formed via auto-oxidation reactions of phenol moieties in the presence of radicals, hydrogen peroxide, and divalent metal ions [19, 20]. Hydroxyl radicals generated from the reaction of hydrogen peroxide with metals such as ferrous ions are also present in foods [21].…”
Section: Main Textmentioning
confidence: 99%
“…In addition, some bioactive peptides prepared by enzymatic methods often have strong ability to chelate metals such as calcium and zinc [31,32]. Liao et al reported that WBP-Zn, a walnut protein zinc-chelating peptide prepared by combining the WBP obtained by an enzymatic method with zinc ion has a better ability of reducing toxicity and better anti-proliferation effects [32].…”
Section: Enzymatic Preparationmentioning
confidence: 99%